2006
DOI: 10.1111/j.1462-2920.2006.01012.x
|View full text |Cite
|
Sign up to set email alerts
|

A double mutant of Pseudomonas putida JLR11 deficient in the synthesis of the nitroreductase PnrA and assimilatory nitrite reductase NasB is impaired for growth on 2,4,6‐trinitrotoluene (TNT)

Abstract: Pseudomonas putida JLR11 can grow on 2,4,6-trinitrotoluene (TNT) as the sole nitrogen source. We created nasB (nitrite reductase), pnrA (nitroaromatic reductase) and pnrA nasB mutants and tested their growth with TNT as the sole N source. The nasB and pnrA mutants grew at a reduced rate on TNT, whereas the double nasB pnrA mutant did not. This suggests that P. putida JLR11 carries out multiple enzymatic attacks on TNT-releasing nitrite and/or ammonium. The PnrA nitroreductase plays a key role in the reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The nitroreductases NfsA and NfsB, together with the N-ethylmaleimide reductase NemA, contributed to the ability of E. coli AB1157 to obtain usable nitrogen from TNT (51). Similarly, the nitroreductase PrnA was shown to be involved in the utilization of TNT as a nitrogen source by P. putida JLR11, and the assimilatory nitrite reductase NasB contributed to the ability of the strain to grow efficiently (14,15). A mechanism for the release of nitrite during the condensation of hydroxylaminodinitrotoluene (the product of nitroreductase activity on TNT) and a Meisenheimer dihydride complex (Fig.…”
Section: Pathways For Nitrotoluene Catabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…The nitroreductases NfsA and NfsB, together with the N-ethylmaleimide reductase NemA, contributed to the ability of E. coli AB1157 to obtain usable nitrogen from TNT (51). Similarly, the nitroreductase PrnA was shown to be involved in the utilization of TNT as a nitrogen source by P. putida JLR11, and the assimilatory nitrite reductase NasB contributed to the ability of the strain to grow efficiently (14,15). A mechanism for the release of nitrite during the condensation of hydroxylaminodinitrotoluene (the product of nitroreductase activity on TNT) and a Meisenheimer dihydride complex (Fig.…”
Section: Pathways For Nitrotoluene Catabolismmentioning
confidence: 99%
“…Two Gram-positive isolates, strains TNT-8 and TNT-32, were able to use TNT as a nitrogen source, but the mechanism of nitrogen assimilation remains unclear (200). More recently, Ramos et al reported that Pseudomonas putida JLR11 (13)(14)(15) and Escherichia coli AB1157 (51) were able to use TNT as a nitrogen source for growth, reducing the nitro group and recovering the ammonium by the use of nitroreductases. The nitroreductases NfsA and NfsB, together with the N-ethylmaleimide reductase NemA, contributed to the ability of E. coli AB1157 to obtain usable nitrogen from TNT (51).…”
Section: Pathways For Nitrotoluene Catabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds are susceptible to the reduction of the nitro side groups to yield hydroxylamino groups. This type of activity is also called nitroreductase activity (6,7,8,9,20,28,34) and will be referred to here as type I hydride transferase activity. Other OYE members have been described to additionally catalyze the nucleophilic attack on the aromatic ring of 2,4,6-trinitrotoluene (TNT) by hydride ions to produce Meisenheimer monohydride and dihydride complexes (13,23,24,29,32,37).…”
mentioning
confidence: 99%
“…Since E. coli is unable to assimilate nitrate or nitrite under aerobic conditions (12), the use of nitrogen from TNT occurred via a metabolic pathway other than the direct release of nitrite. Recent reports have postulated the partial reduction of one or more nitro groups of TNT to its hydroxylamino moiety and the subsequent release of ammonium from the aromatic ring (3)(4)(5)16), probably through a Bamberger-like rearrangement (11). Next, ammonium was likely used as a nitrogen source by E. coli via the glutamine synthetase/glutamate synthase pathway (16).…”
mentioning
confidence: 99%